Association of Smoking-Related Knowledge, Attitude, and Practices (KAP) with Nutritional Status and Diet Quality: A Cross-Sectional Study in China. (21st August 2019) - Haq, Ijaz ul; Liu, Yu; Liu, Min; Xu, Haifeng; Wang, Hui; Liu, Chunlan; Zeb, Falak; Jiang, Pan; Wu, Xiaoyue; Tian, Yuanrui; Li, Mengxia; Li, Qun; et al.
Abstract : Background . Smoking is the second leading cause of death. Limited studies are available about smoking and overall diet quality. The current study was aimed at finding an association of s-KAP (smoking-related knowledge, attitude, and practices) with nutritional status and diet quality. Methodology . The current study was a cross-sectional community-based study conducted in Jurong city, China. Validated questionnaires were used for the collection of data regarding s-KAP and dietary intake. Correlation and multivariate linear regression analysis were used for the association of s-KAP scores with diet quality scores and nutritional status. Results . The total numbers of participants were 7998 with a mean age of 59.3±11.4 years, including 38.5% males and 41.5% females. s-KAP scores were categorized into two groups, i.e., High s-KAP group and low s-KAP group. The High s-KAP group had significantly higher ( P<0.05 ) diet scores and BMI but lower ( P<0.05 ) WC (waist circumference) and WHR (waist to hip ratio) than the Low s-KAP group. Independent positive association ( P<0.05 ) of s-KAP scores with diet scores was observed after the adjustment for age, gender, physical activity, alcohol consumptions, monthly income, and anthropometric measures (BMI, WC, and WHR). Similarly, smoking was positively associated ( P<0.05 ) with diet scores after adjustment for covariates. Conclusion . In conclusion, the higher s-KAP scores indicated more knowledge regarding the harmful consequences of the smoking outcomes, positive attitude, less smoking practices, and having a good plan to quit smoking. Individuals with high s-KAP scores had good diet quality and lower adiposity measures. Furthermore, s-KAP scores and smoking status were having an independent positive association with diet scores.